Web frontend for CleverMiner - Vala, Lukáš (2025)
This thesis presents the development of a web front-end for CleverMiner, a Python-based rule mining library currently used primarily in an academic setting at the Prague University of Economics and Business. The main challenge while working with CleverMiner is the fact that programming knowledge is required in order to use it, which limits it's accessibility for non-technical users. To address this issue, a web interface has been designed and implemented to bridge the gap between ordinary users and the CleverMiner library. The solution includes a REST API for back-end interaction and a pilot front-end enabling users to create and manage analysis tasks, modify parameters, and interpret results. The particular focus was on the 4ft-Miner GUHA procedure and exposing all of its functionality through the front-end. The result is a modern, accessible tool that makes rule mining with CleverMiner more approachable for a wider audience.